Perancangan dan Pembuatan Video Promosi Wisata Kota Bengkulu Menggunakan metode ADDIE - Tony Wibowo; Asep Didi Kurniadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Bengkulu is a city located on the island of Sumatra which has a variety of tribes, cultures and languages ​​in it. Bengkulu itself has a charm of beauty that spoils the eyes, especially in the field of tourism. There are many beautiful tourist destinations in the city of Bengkulu, but due to the lack of exploration of these destinations, the city of Bengkulu looks like a quiet city without any recreation areas for refreshing during the holidays. With these problems, there must be an innovation in the field of media and publications to help create a promotional media in the form of promotional videos about tourism in the city of Bengkulu. Which later will be implemented into a youtube platform. This study uses the ADDIE method (Analysis, Design, Development, Implementation, Evaluation). The results obtained after this promotional video was successfully designed, the author hopes to be a reference or encouragement to the tourism office and also the Bengkulu city government to introduce more tourism in the city of Bengkulu